Supracrural Rerouting as a Technique for Resolution of Posterior Urethral Disruption Defects - Hosseini, Seyed Jalil; Rezaei, Alireza; Mohammadhosseini, Mojtaba; Rezaei, Iraj; Javanmard, Babak (Urology Journal, 2009)
Introduction: Selection of an acceptable method for the treatment of posterior urethral disruption defects would be highly desirable. We determined the efficacy and success rate of some techniques including supracrural rerouting for removing of these defects among our patients. Materials and Methods: Records of 200 consecutive men treated with anastomotic urethroplasty for traumatic posterior urethral strictures were reviewed at our teaching hospital. Prior treatment, surgical approach, and ancillary techniques required during reconstruction were evaluated. Results: Success rate due to posterior urethral reconstruction was achieved in 78.0% of cases. Supracrural urethral rerouting was performed in 11 patients (5.5%), of whom 7 sustained recurrent stricture requiring intervention. The highest success rate of defect resolving was reported by urethral mobilization (92.4%). Conclusion: Supracrural rerouting is not an acceptable technique and can result in postoperative complications such as recurrent stricture in most of the patients with posterior urethral disruption defects.